The burden of diabetes and the chance of a previous stroke: thrombolysis for recurrent stroke in diabetics - Filipov, Alexandra; Ebert, Anne; Neumaier-Probst, Eva; Alonso, Angelika (Journal of stroke and cerebrovascular diseases, 2018)
BACKGROUND: Intravenous thrombolysis with recombinant tissue plasminogen activator is still not approved by the European Medicines Agency for patients with diabetes mellitus and previous stroke. We assessed functional benefit and potential risk of thrombolysis in patients with diabetes and previous stroke and the influence of age, preexisting diabetic damage, as well as acute and chronic hyperglycemia on outcome, symptomatic intracranial hemorrhage, and in-hospital mortality. - METHODS: We analyzed 527 consecutive patients treated with thrombolysis for acute stroke. Poor outcome was defined as deterioration of prestroke modified Rankin Scale (mRS) to 3 or greater at discharge. Symptomatic intracranial hemorrhage was defined according to the Safe Implementation of Thrombolysis in Stroke-Monitoring Study criteria. - RESULTS: Of the patients, 35.9% were diabetic and 33.2% had previous stroke. Of these patients, 14.4% were diabetics with previous stroke (index group). The rate of patients with poor functional outcome at discharge, symptomatic intracranial hemorrhage, or mortality did not differ between the index group and patients with either diabetes or previous stroke in 2 × 2 comparisons. Diabetics with first-ever stroke showed significantly more symptomatic intracranial hemorrhage (9.7%, P < .001) than the other groups, poorer functional recovery (P = .036), and the highest rate of mortality (12.4%, P < .001). Significant predictors for poor outcome were age (P < .001) and HbA1c (P = .013), for symptomatic intracranial hemorrhage HbA1c (P = .006) and for mortality acute hyperglycemia (P = .001) and age (P = .004). - CONCLUSION: Diabetics with previous stroke should not be withheld from intravenous thrombolysis. The risk of complications derives primarily from poor long-term metabolic control rather than from acute hyperglycemia or from previous stroke.
Gesehen am 17.04.2020